The expression, localization and function of α7 nicotinic acetylcholine receptor in rat corpus cavernosum. (24th August 2017) - Faghir‐Ghanesefat, Hedyeh; Rahimi, Nastaran; Yarmohammadi, Fatemeh; Mokhtari, Tahmineh; Abdollahi, Ali Reza; Ejtemaei Mehr, Shahram; Dehpour, Ahmad R.
Abstract: Objectives: Alpha7 nicotinic acetylcholine receptor (α7‐nAChR), an emerging pharmacological target for a variety of medical conditions, is expressed in the most mammalian tissues with different effects. So, this study was designed to investigate the expression, localization and effect of α7‐nAChR in rat corpus cavernosum (CC). Methods & Key findings: Reverse transcription polymerase chain reaction (RT‐PCR) revealed that α7‐nAChR was expressed in rat CC and double immunofluorescence studies demonstrated the presence of α7‐nAChR in corporal neurons. The rat CC segments were mounted in organ bath chambers and contracted with phenylephrine (0.1 μm ‐300 μm ) to investigate the relaxation effect of electrical field stimulation (EFS, 10 Hz) assessed in the presence of guanethidine (adrenergic blocker, 5 μm ) and atropine (muscarinic cholinergic blocker, 1 μm ) to obtain non‐adrenergic non‐cholinergic (NANC) response. Cumulative administration of nicotine significantly potentiated the EFS‐induced NANC relaxation (‐log EC50 = 7.5 ± 0.057). Whereas, the potentiated NANC relaxation of nicotine was significantly inhibited with different concentrations of methyllycaconitine citrate (α7‐nAChR antagonist, P  < 0.05) in preincubated strips. L‐NAME (non‐specific nitric oxide synthase inhibitor, 1 μm ) completely blocked the neurogenic relaxation induced by EFS plus nicotine. Conclusion: To conclude α7‐nAChR is expressed in rat CC and modulates the neurogenic relaxation response to nicotine.